Double pull specimen more suitable for measuring bond-slip relationship of FRP-to-concrete interface - Yang, Qi-fei; Lu, Xiao-hua; Xiong, Guang-jing (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2010)
A new “conceptual” design named “double pull” specimen was proposed in order to measure the bond-slip ( σ−τ ) relationship of fiber reinforced polymer (FRP)-to-concrete interface more accurately. A finite element analysis (FEA) was performed for preliminarily evaluating the suitability of the proposed conceptual double pull specimen. Through the FEA, it was indicated that the FRP-to-concrete interface of the proposed conceptual specimen might subject to a much higher load level than that of the most commonly used simple shear specimen, showing a great potential for measuring σ−τ relationship more accurately. In the light of the conceptual specimen, a kind of “practical” double pull specimen was developed and proved to be more suitable for measuring σ−τ relationship through an exploratory experimental study with 20 specimens. Consequently, an experimental program with 10 double pull specimens was performed for measuring the ultimate slip σ u which was difficult to capture by using the existing specimens. It is shown that the range of σ u is 0.31–0.52 mm based on the test results. The suggestion for improving the measure method is also put forward.